The development of the global education system and pedagogical science in the modern era - Norqulova , Madina; Ochildiyeva , Iroda (Journal of Pedagogical and Philological Research, 2026)
This scientific article analyzes the current development trends of education systems around the world and the progress of pedagogical science. The impact of globalization, digitalization, and innovative technologies on educational content, forms, and teaching methods is discussed. Special attention is paid to the competency-based approach, inclusive education, and the concept of lifelong learning as key factors in improving the quality of education.